2015
DOI: 10.4238/2015.december.14.18
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of cisplatin-induced autophagy sensitizes cervical cancer cells to cisplatin

Abstract: ABSTRACT. Development of chemoresistance is a major obstacle that leads to the recurrence and progression of cervical cancer (CC). Autophagy, meaning, "eating of self", has shown paradoxical functions in tumors. In this study, we first investigated the process of autophagy induction by cisplatin in CC cells. Next, we investigated the role of autophagy in cisplatinsensitivity of CC cells via blockage of cisplatin-induced autophagy. The results demonstrated that cisplatin induces autophagy in CC HeLa cells via u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Cisplatin induced autophagy in a concentration-dependent manner in the examined cells, as demonstrated by the western blot results for the autophagy markers LC3-I, LC3-II and p62. This compound has previously been demonstrated to induce autophagy in various types of cancer cells, such as ovarian cancer cells and osteosarcoma cancer cells (35,36), and another study indicated that autophagy serves a protective role in cisplatin resistance (34). The results of the present study demonstrated that the blockade of autophagy promoted cisplatin-induced cell death in SKOV3 and SKOV3/DDP cells, and partially re-sensitized cisplatin-resistant SKOV3/DDP cells.…”
Section: Discussionsupporting
confidence: 68%
“…Cisplatin induced autophagy in a concentration-dependent manner in the examined cells, as demonstrated by the western blot results for the autophagy markers LC3-I, LC3-II and p62. This compound has previously been demonstrated to induce autophagy in various types of cancer cells, such as ovarian cancer cells and osteosarcoma cancer cells (35,36), and another study indicated that autophagy serves a protective role in cisplatin resistance (34). The results of the present study demonstrated that the blockade of autophagy promoted cisplatin-induced cell death in SKOV3 and SKOV3/DDP cells, and partially re-sensitized cisplatin-resistant SKOV3/DDP cells.…”
Section: Discussionsupporting
confidence: 68%
“…91,92 A recent study suggested that Cis induces autophagy in HeLa cells via upregulating the formation of autophagic vesicles, promoting the conversion of LCI to LCII and increasing the expression of the autophagy-related ATG7 gene. 82 Our findings provide evidence that the autophagy induced by Cis …”
Section: Combination Of Cis and Rgo-agnps Induces Accumulation Of Autmentioning
confidence: 51%
“…Autophagy is a process in which cellular material transferred into lysosomes for degradation and amount of studies illustrated that autophagy plays extremely important roles in cancer cells [32]. In addition, LC3-I and LC3-II are two important marker factors in autophagy and autophagy promoted the conversion of LC3-I to LC3-II [33]. Transfection with EGFP-LC-3, the phagosome-specific marker, could trace the change of LC-3, by which to determine the situation of autophagy [34].…”
Section: Discussionmentioning
confidence: 99%